Implementation of Si Kepul Technology for Optimizing Waste Management at SMA Telkom Bandung - Ajri Inda Robby; Muhammad Akram Septi Pratama; Fauzi Fikri Wicaksono; Galih Ashari Rakhmat (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2025)
SMA Telkom Bandung faces challenges in waste management, particularly in waste separation and collection, which remain suboptimal. To address this issue, the Si Kepul application was developed as a technology-based solution integrating both mobile and web platforms. The mobile app allows school residents to sell waste directly to local collectors, featuring location tracking, real-time waste price catalogs, and a digital payment system. The web platform enables administrators to monitor activities and manage waste data efficiently. This system was implemented through an iterative approach involving active participation from students, teachers, and school staff. As a result, improvements were observed in waste management efficiency, environmental awareness, and economic opportunities. The system aims to enhance school waste management and serves as a potential model for technology-driven waste solutions in educational institutions.